2004
DOI: 10.1051/limn/2004025
|View full text |Cite
|
Sign up to set email alerts
|

Organic matter decomposition by fungi in a Mediterranean forested stream : contribution of streambed substrata

Abstract: Aquatic microfungi play a fundamental role in organic matter decomposition in fluvial ecosystems. These micro-organisms degrade leaf recalcitrant compounds like lignin, thereby enhancing the utilization of organic material by the microbial community. The main input of allochthonous organic matter in Mediterranean streams occurs during the autumn. In-stream breakdown processes can be affected by high physical abrasion during flooding but changes in stream water chemistry may also affect decomposition enzymatic … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
13
0

Year Published

2009
2009
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 22 publications
(15 citation statements)
references
References 32 publications
2
13
0
Order By: Relevance
“…Although this heterotrophic episode is related to leaf litter input and accumulation in the stream, microbial benthic communities also showed active decomposition activity during the winter. At this time, the decomposition of lignocellulose (phenol oxidase activity) and organic phosphorus compounds (phosphatase) was greatest in coarse substrata where fine detritus accumulated (Artigas, Romaní & Sabater, 2004).…”
Section: Discussionmentioning
confidence: 99%
“…Although this heterotrophic episode is related to leaf litter input and accumulation in the stream, microbial benthic communities also showed active decomposition activity during the winter. At this time, the decomposition of lignocellulose (phenol oxidase activity) and organic phosphorus compounds (phosphatase) was greatest in coarse substrata where fine detritus accumulated (Artigas, Romaní & Sabater, 2004).…”
Section: Discussionmentioning
confidence: 99%
“…These autotrophic lake biofilms seem to be a rich source of fungal biodiversity and pose promising target habitats for future studies. Biofilms (in our case mainly littoral periphyton and epilithic biofilms) have been rarely examined for fungi, and only a few studies on stream ecosystems have investigated the fungal occurrence (measured as ergosterol) on substrates other than leaves (Tank and Dodds 2003;Artigas et al 2004;Aguilera et al 2007;Frossard et al 2012). In lakes and streams, periphyton can contribute substantially to the primary production of the whole ecosystem (Lalonde et al 1991;Vadeboncoeur et al 2007 and references therein; Vis et al 2007) and can be the primary food source for macrozoobenthic grazers (Cattaneo and Mousseau 1995).…”
Section: Biofilm (Periphyton)mentioning
confidence: 99%
“…Indeed, nitrogen effect (including nitrate), have already been observed in other studies working on microbial communities from forest soils (Baldrian, 2006;Gallo, Amonette, Lauber, Sinsabaugh, & Zak, 2004;Sinsabaugh, 2010) and streams (Artigas et al, 2004 our study showed also that after a twofold increase of nitrate concentrations probably resulting from the rainfall event occurring at week 2, laccase activity tended to be inhibited (Pearson, r = À.497, p < .05), whereas peroxidase and phenol oxidase activities tended to be stimulated (Pearson, r = .807 and r = .549 respectively, p < .05, RDA UpsDws , Figure 5b). Indeed, nitrogen effect (including nitrate), have already been observed in other studies working on microbial communities from forest soils (Baldrian, 2006;Gallo, Amonette, Lauber, Sinsabaugh, & Zak, 2004;Sinsabaugh, 2010) and streams (Artigas et al, 2004 our study showed also that after a twofold increase of nitrate concentrations probably resulting from the rainfall event occurring at week 2, laccase activity tended to be inhibited (Pearson, r = À.497, p < .05), whereas peroxidase and phenol oxidase activities tended to be stimulated (Pearson, r = .807 and r = .549 respectively, p < .05, RDA UpsDws , Figure 5b).…”
Section: Discussionmentioning
confidence: 54%
“…Amongst those pollutions, the effects of nutrients on aquatic fungal communities is certainly one of the most studied (Gessner et al, 1999). Although nutrient enrichment (by phosphorus and nitrogen) is commonly associated with increases in fungal biomass, diversity, and activity (Artigas, Roman ı, & Sabater, 2004;Hagen, Webster, & Benfield, 2006;Magbanua, Townsend, Blackwell, Phillips, & Matthaei, 2010), some studies also observed a negative effect of the nutrients, depending on the concentration and nature of the amendments (Baldy, Chauvet, Charcosset, & Gessner, 2002;Duarte, Pascoal, Garab etian, C assio, & Charcosset, 2009b). For instance, high nitrate and ammonium concentrations in eutrophic streams have been shown to decrease fungal diversity and biomass, as well as their potential for decomposing leaf litter (Baldy et al, 2002;Duarte, Pascoal, Garab etian, et al, 2009b).…”
mentioning
confidence: 99%